Validity and Reliability of the Spence and Robbins Workaholism Battery: A Study in Malaysian Employees - Almustafa, Ammar; Ke, Guek Nee (UI Scholars Hub, 2022)
This psychometric study aims to contribute to the evolving cross-cultural definition of workaholism by exploring the reliability and validity of using the Workaholism Battery (WorkBAT; Spence & Robbins, 1992) in a sample of 183 full-time white-collar workers in Malaysia. Using data from online surveys, collected from full-time white-collar workers in the private and public sectors, factor analysis was used to indicate factor solutions contributing to the definition of workaholism based on the Spence and Robbins (1992) model of high work involvement, high work drive, and low work enjoyment. The study identified three factors and reassigned the items between them into work enjoyment, work drive, and work withdrawal. A 2-step cluster analysis identified four profiles of work adaptability as workaholics, enthusiastic workaholics, anxious workers, and moderate workers. Criterion validity with working hours was not established indicating workaholism as a distinct construct as suggested by previous studies. Our analysis produced a 3-factor solution suggesting a further syndromic view of the addiction to work. The addition of the third factor of work withdrawal indicates a further shift into looking at workaholism with a clinical lens.